2017
DOI: 10.1016/j.joca.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Role of the C-C chemokine receptor-2 in a murine model of injury-induced osteoarthritis

Abstract: Objective We previously found in our embryonic studies that proper regulation of the chemokine CCL12 through its sole receptor CCR2, is critical for joint and growth plate development. In the present study, we examined the role of CCR2 in injury-induced-osteoarthritis (OA). Method We used a murine model of injury-induced-OA (destabilization of medial meniscus, DMM), and systemically blocked CCR2 using a specific antagonist (RS504393) at different times during disease progression. We examined joint degenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 47 publications
4
74
0
Order By: Relevance
“…In the current issue of Osteoarthritis and Cartilage , Longobardi and colleagues report the first studies with prolonged therapeutic administration of a CCR2-RA (RS-504393) in the murine DMM model [10]. They found that sustained pharmacological blockade of CCR2 mimics the findings in Ccr2 null mice.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the current issue of Osteoarthritis and Cartilage , Longobardi and colleagues report the first studies with prolonged therapeutic administration of a CCR2-RA (RS-504393) in the murine DMM model [10]. They found that sustained pharmacological blockade of CCR2 mimics the findings in Ccr2 null mice.…”
mentioning
confidence: 99%
“…It should also be considered that CCR2 is a widely expressed molecule, present on monocytes, T cells, neurons, osteoclasts, and chondrocytes [4, 10]. In cartilage, a number of chemokines, including the three CCR2 ligands, are upregulated in rodent models of OA, but the role of chemokine signaling within cartilage in OA pathogenesis remains unclear [4, 10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Timing of genetic deletion or treatment may be critical for disease outcome. In this issue, we report the failure to show a significant reduction in cartilage degradation in Ccl2 and Ccr2 constitutive knockout mice [15], yet targeting the pathway after the initial injury appears to be effective at inhibiting disease [16]. In other words, molecules may have different roles at different times of disease.…”
mentioning
confidence: 99%
“…A recent review on standardizing OA definition highlights the need to stage disease, separating OA development, OA progression and early detection (Kraus et al 2015). In addition, it was recently found different outcomes between short-and longterm inhibition of CCR2, suggesting this chemokine may play different roles during OA progression (Longobardi et al 2016). For example, is the beneficial effect of a specific treatment due to a protection against initiation of AC lesions, or because of interference with a specific event involved in progression of joint degeneration?…”
Section: Introductionmentioning
confidence: 99%